Janus Kinase-2 V617F Mutation and Antiphospholipid Syndrome in Cerebral Sinus Venous Thrombosis: Natural History and Retrospective Bicenter Analysis - Orion, David; Itsekson-Hayosh, Ze'ev; Peretz, Shlomi; Mendel, Rom; Yaniv, Gal; Attia, Moshe; Grizim-Merkel, Drorit (Frontiers in Neurology, 2022)
Background Cerebral sinus venous thrombosis (CSVT) is a rare neurovascular entity, usually associated with acquired or genetic hypercoagulable states. In up to 30% of the cases it remains idiopathic. Bone marrow proliferation disorders that are associated with Janus Kinase 2 V617F mutation (JAK-2) are known causes of the systemic and cerebral thrombosis—at times despite normal blood counts—for which hematologic treatment exists. However, JAK-2 prevalence in the CSVT cases is not clear. Methods In this retrospective analysis, data of 236 patients with CSVT admitted to two tertiary centers between 2010 and 2020 were analyzed, with emphasis on laboratory and imaging data and clinical and interventional outcomes. Results A total of 236 patients were included in the analysis. The patients' median age was 42 years and the average age was 44 years (±19 years), with 59% female patients. JAK-2 positivity rate was 18% (among 77 patients tested for the mutation). Patients with normal blood counts on presentation comprised 36% of the JAK-2 positive cases. Other hypercoagulability states were also investigated, with the antiphospholipid syndrome (APLA) showing the highest prevalence (11%) followed by other etiologies including oral contraceptive use, Factor V Leiden, prothrombin mutation, and malignancy. Selected JAK-2, APLA, and prothrombin mutation cases showed a more severe clinical course. Conclusion JAK-2 mutation is underdiagnosed and its screening may be warranted in the cases of idiopathic CSVT, even despite normal blood counts, to allow disease-modifying treatment and blood cell count monitoring. JAK-2, APLA, and prothrombin mutation may be associated with a more complicated clinical course.